Influence of Compensation on Work Performance in the District Office of Bissappu, Bantaeng Regency - Widya Permata Indah Sari; Jamaluddin Jamaluddin; Sirajuddin Saleh; Sitti Hardiyanti Arhas (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
The potential of every human resource in each office must be utilized as well as possible so as to provide optimal output. This study aims to determine the effect of compensation on employee performance in the Bissappu District Office, Bantaeng Regency. This study uses a quantitative approach with a population of 52 and determining the amount of 5 percent of the population so that 46 samples are obtained. Of the 46 samples 44 of them were made as Respondents and 2 were used as Informants. Data collection techniques observation, questionnaire, interview, and documentation, while the data analysis technique used is the percentage statistics. The results showed that the effect of compensation in the District Office of Bissappu in Bantaeng Regency was classified as very high in terms of indicators of direct compensation and indirect compensation. The work performance of employees in the Bissappu District Office of Bantaeng Regency is classified in the very high category in terms of indicators of work quality, work quantity, level of reliability, and attitude. Hypothesis testing results indicate that there is a significant relationship between compensation for employee performance in the District Office of Bissappu, Bantaeng Regency.